Economic paradigms and economic communications - Petr Wawrosz; Radim Valenchik; Ondrei Roubal; Svetlana Sazanova (Управление)
The development of modern economic theory is influenced by various factors of the external and internal environment. The factors of the external environment include: changes in the practice of economic entities, global economy, in the institutional environment, technological changes. The factors of the internal environment include: changes in the field of scientific knowledge in general, as well as changes in the methodology of economic science itself. The main driving force behind the development of economic theory is the evolution of economic paradigms, which has an impact on the methodological choice of researchers, their scientific worldview. An important component of human economic activity are economic communications, the essence and content of which have not been yet sufficiently studied from a theoretical point of view. Since economic communications are closely related to the behavior of economic agents, which affects, in turn, the results of economic activity, their study is an urgent task. The subject of research in the article is the relationship of economic paradigms and ideas about the essence of economic communication. The purpose of the article is to study the influence of the evolution of economic paradigms on the development of scientific ideas about economic communication. The authors have applies following research methods in the scientific paper: the method of rational reconstruction of science, the method of comparative analysis, the method of scientific abstraction and others. The relationship between the evolution of economic paradigms, theories of behavior of economic agents and the understanding of the role of economic communications in economic activity have been revealed. The authors investigated economic communications in the context of the theory of full, limited, procedural rationality, organic irrationality, as well as in the context of the theory of productive consumption. The main scientific results consist in identifying features in the understanding of the essence of economic communications from the point of view of various theories. The results obtained are the basis for the study of the systemic and humanistic foundations of economic communications, as well as the development of recommendations for improving economic communications.